Impact of Lerner Index, HHI Index, and opportunity cost of bank reserve on the net interest margin of commercial banks - Phạm Minh Điển; Dương Thị Kim Hoàng; Dương Quỳnh Nga (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2020)
This study examines the impact of Lerner Index, HHI Index, and the opportunity cost of reserves on net interest margin (NIM) of commercial banks. Other determinants of their net interest margin (NIM) are also investigated as control variables in the study. This study uses the PCSE model for equilibrium data from 27 joint-stock commercial banks in Vietnam for the period of 2011-2015 to identify factors that affect the marginal interest rate of commercial banks. The results show that factors including the Lerner Index, HHI Index, the opportunity cost of reserves, the operating cost are correlated with the net interest margin (NIM). While there is an inverse relationship between the market share and the net interest margin (NIM). The two factors including HHI Index and credit risk don’t affect the net interest margin (NIM) of commercial banks.